Empowerment of Salted Fish Processors to Support Marine Tourism at Sikabau Beach, Nagari Ranah Koto Tinggi, Koto Balingka Subdistrict, Pasaman Barat Regency - Ardiansyah, Gari; Zulkarnain, Zulkarnain; Yulindra, Eni (Fakultas Perikanan dan Kelautan Universitas Riau, 2025)
The potential for developing marine tourism in Sikabau Beach focuses on integration with the local salted fish processing industry and the importance of synergy between the two sectors, considering that Jorong Sikabau has stunning natural beauty and maritime traditions, including salted fish processing that has been passed down from generation to generation. However, the salted fish processing industry still faces challenges, such as limited market access, lack of technical knowledge, and inadequate infrastructure. This study aims to describe the tourism picture and characteristics of salted fish processors and analyze the empowerment of salted fish processors. The method used in this study is a case study method using a qualitative approach. The selection of informants in this study was purposive. The data analysis used was qualitative, starting from data reduction, data display, and drawing conclusions. The study results showed that the characteristics of Sikabau Beach marine tourism are mangrove forest tourism, Batu Kajang, and the estuary of Sikabau Beach. The attributes of salted fish processing businesses are that they still carry out the processing process traditionally. The empowerment carried out for salted fish processors is training in processing fish-based products and their marketing, fish packaging, and how to reproduce good processed food. The programs that have not been implemented are business strengthening and strengthening the added value of products. Therefore, there needs to be support from the government that focuses more on skills training for salted fish processors and the development of adequate infrastructure for salted fish processors.